2022
DOI: 10.3390/ijerph19148239
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking in Response to COVID-19: Examining Co-Morbid Medical Conditions and Risk Perceptions

Abstract: During the initial wave of the Coronavirus Disease 2019 (COVID-19) pandemic in the U.S., information was mixed about the relative COVID-19 risks and potential benefits associated with cigarette smoking. Therefore, we sought to understand individual differences in the impact of COVID-19 on cigarette smoking in a sample of adults who reported recent use, with a particular focus on chronic medical conditions likely associated with increased COVID-19 risk. Participants completed an online survey of smoking behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…The latter aligns with data reported by Fucito et al and Kowitt et al which found that Black participants reported tobacco use reductions and intention to quit during the pandemic compared to White participants. 63 , 64 For the other two lifestyle factor assessed, we observed positive trends: overall, more participants reported increasing fruit and vegetable consumption and decreasing alcohol consumption as compared to the number of participants reporting decreasing consumption of fruit and vegetables and increasing consumption of alcohol. No race or ethnicity differences were observed.…”
Section: Discussionmentioning
confidence: 77%
“…The latter aligns with data reported by Fucito et al and Kowitt et al which found that Black participants reported tobacco use reductions and intention to quit during the pandemic compared to White participants. 63 , 64 For the other two lifestyle factor assessed, we observed positive trends: overall, more participants reported increasing fruit and vegetable consumption and decreasing alcohol consumption as compared to the number of participants reporting decreasing consumption of fruit and vegetables and increasing consumption of alcohol. No race or ethnicity differences were observed.…”
Section: Discussionmentioning
confidence: 77%
“…Under COVID-19, the uprising ratio of IGD, along with other kinds of addiction, such as alcohol (Stockwell et al, 2021), smoking (Fucito et al, 2022), drug (Tan et al, 2021), and gambling (Bellringer et al, 2021), reflected people's intention to occupy their life with such addictions in lockdown life and to avoid suffering caused by terror from the virus. How resilience helped people to confront adversity positively might be in three steps.…”
Section: Discussionmentioning
confidence: 99%